(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Although the term "business model" is commonly used in the industry, the scholarly book on the issue is fragmented and complicated by various definitions and construct boundaries. In this study, we review existing research and reconstruct the firm model from an entrepreneurial standpoint. To help understand how professional managers ensure concerning business strategies, we provide us the findings of an applied linguistics of 151 surveys of practitioners and researchers. We determine that the basic parameters of the financial model are capacity organization, feedforward structure, and function of the number, and we investigate the nature and effects of volumetric dominance on corporate features and behavior. These findings open up new paths for theoretically studies and subsequent study in enterprise by relating the firm model to motivation, opportunity cross, and work productivity.